Discovery of the gut microbial signature driving the efficacy of prebiotic intervention in obese patients. Issue 11 (10th February 2020) - Rodriguez, Julie; Hiel, Sophie; Neyrinck, Audrey M; Le Roy, Tiphaine; Pötgens, Sarah A; Leyrolle, Quentin; Pachikian, Barbara D; Gianfrancesco, Marco A; Cani, Patrice D; Paquot, Nicolas; Cnop, Miriam; Lanthier, Nicolas; et al.
Abstract : Objective: The gut microbiota has been proposed as an interesting therapeutic target for metabolic disorders. Inulin as a prebiotic has been shown to lessen obesity and related diseases. The aim of the current study was to investigate whether preintervention gut microbiota characteristics determine the physiological response to inulin. Design: The stools from four obese donors differing by microbial diversity and composition were sampled before the dietary intervention and inoculated to antibiotic-pretreated mice ( hum-ob mice; humanised obese mice). Hum-ob mice were fed with a high-fat diet and treated with inulin. Metabolic and microbiota changes on inulin treatment in hum-ob mice were compared with those obtained in a cohort of obese individuals supplemented with inulin for 3 months. Results: We show that hum-ob mice colonised with the faecal microbiota from different obese individuals differentially respond to inulin supplementation on a high-fat diet. Among several bacterial genera, Barnesiella, Bilophila, Butyricimonas, Victivallis, Clostridium XIVa, Akkermansi a, Raoultella and Blautia correlated with the observed metabolic outcomes (decrease in adiposity and hepatic steatosis) in hum-ob mice. In addition, in obese individuals, the preintervention levels of Anaerostipes, Akkermansia and Butyricicoccus drive the decrease of body mass index in response to inulin. Conclusion: These findings support that characterising the gut microbiota prior to nutritional intervention with prebiotics is important to increase the positive outcome in the context of obesity and metabolic disorders.